The Economics of Hospital Trips and Health Care Reform - Andreas Million; Ralph Rotte; Klaus F. Zimmermann (Institute for the Study of Labor (IZA), 1998)
One cornerstone of current attempts to reform the German public health care system by introducing private insurance schemes is the assumption that economic incentives play an important role in individual decision-making about using medical help. This hypothesis is examined for the case of demand for hospital care which covers the largest part of public insurance expenditures. The paper applies various methods for count data analysis of the frequency of hospital trips. Contrary to comparative studies for other countries, we find that there is no significant impact of insurance schemes on hospitalization. Therefore, the current efforts to reduce expenditures by relying on consumer behaviour are unlikely to work.
Keywords: I18; I12; I11; 330; health care reform; hospitalization; hospital cost inflation; Gesundheitsökonomik; Krankenhaus; Nachfrage; Krankenhauskosten; Gesundheitsreform; Schätzung; Deutschland